Rompendo velhas mortalhas: a violência contra a mulher e sua relação com o Imaginário Androcêntrico de Deus na Igreja Metodista do Chile. - Martínez, Raquel Carmen Riquelme (2004)
The objective of this thesis is to explore and analyze violence against women and the relationship that exists between this conduct and the androcentric image of God, in a specific context, the men and women of the Methodist Church of Chile. We have undertaken an analytic reading of the way in which women and men relate to each other, in matrimony, and women, men and God. The objective is to investigate the similarities that exist between the hierarchical attitudes of men in society, in the family, and in the model of an androcentric God present in the collective imagination of Chilean society. This thesis has been developed using as its principal idea the image and androcentricity of God and the variables that this image gives way to: androcentric ideology, over-rating of masculine hegemony and language, and legitimizing of violence against women. These situations are analyzed from a specific context within the Methodist Church of Chile, which served as the motivation to observe the legitimacy of the problem within a wider context: the predominately androcentric Chilean society. In this way, the search for the elements will lead us to prove the hypothesis which we have set forth in which we will enunciate some anthropological elements, heritage of the Spanish and Indigenous traditions which were fundamental in the formation of the Chilean ethos and idiosyncrasy. For the analysis and critique of the imaginary masculinity of God, we privilege feminist theology. For the concept of violence in which the idea of power is inserted, we deem it important to consider the micro-powers involved in the violence against women fundamentally explicit at the level of micro-structures, although it in fact legitimizes the level of macro-structures, from the patriarchal/traditional discourses of religion and theology. The intention of this thesis is to contribute to the pastoral, theological reflection from a woman s perspective, trying to offer elements to the debate on the path toward overcoming violence.(AU)